Neurotransmitters as Modulators of Neural Progenitor Cell Proliferation During Mammalian Neocortex Development - Xing, Lei; Huttner, Wieland B. (Frontiers in Cell and Developmental Biology, 2020)
Neural progenitor cells (NPCs) play a central role during the development and evolution of the mammalian neocortex. Precise temporal and spatial control of NPC proliferation by a concert of cell-intrinsic and cell-extrinsic factors is essential for the correct formation and proper function of the neocortex. In this review, we focus on the regulation of NPC proliferation by neurotransmitters, which act as a group of cell-extrinsic factors during mammalian neocortex development. We first summarize, from both in vivo and in vitro studies, our current knowledge on how γ-aminobutyric acid (GABA), glutamate and serotonin modulate NPC proliferation in the developing neocortex and the potential involvements of different receptors in the underlying mechanisms. Another focus of this review is to discuss future perspectives using conditionally gene-modified mice and human brain organoids as model systems to further our understanding on the contribution of neurotransmitters to the development of a normal neocortex, as well as how dysregulated neurotransmitter signaling leads to developmental and psychiatric disorders.